Ambient air quality in the Republic of Macedonia from the perspective of EU directive - Bojkovska, Radmila; Mitreski, Kosta (IEEE, 2012)
In September 1996 the EU adopted Framework Directive 96/62/EC (FWD)[1] that defines the key principles of and general requirements for air quality assessment and management in subsequent (Daughter) Directives that lay down limit levels and specify in more detail the requirements concerning each of the pollutants declared in the FWD. The requirements of Directive 96/69/EC do not specify any detailed rules for zone delineation. In this paper we analysis the ambient air quality on the Republic of Macedonia. We have made analysis of the Directives’ requirements in respect of air quality management area delineation - zones and agglomerations. The evaluation is made on the basis of the regular measurements obtained from the three existing measuring networks as well as via measurements of the emissions from stationary and mobile sources in several years period. Results from the analysis of SO2, NO2, NOx, PM10 and ozone concentrations are presented both for specific regions and on the entire state territory. Delineation on zones and agglomerations according to statistical regions is also performed, in line with the preliminary assessment of the air quality according to the measured parameters. We end with several recommendations for improvement of air quality in the given region and for future research work based on these results.
Keywords: Ambient air quality, preliminary assessment, SO2, NO2, PM10, zones, agglomerations, models